Organic Fertilization Assembles Fungal Communities of Wheat Rhizosphere Soil and Suppresses the Population Growth of Heterodera avenae in the Field - Qiu, Wei; Su, Huiqing; Yan, Lingyun; Ji, Kaiyan; Liu, Qian; Jian, Heng (Frontiers in Plant Science, 2020)
Heterodera avenae (cereal cyst nematode, CCN) infects wheat and other cereal crops and causes severe losses in their yield. Research has shown that CCN infestations can be mitigated by organic fertilization in wheat fields, but the mechanisms underlying this phenomenon are still largely unknown. In this study, the relationships among CCN, soil properties, and soil fungal communities with organic fertilizer (OF) or chemical fertilizer (CF) and without fertilizer (CK), were investigated for two years in a wheat field in Henan province, China. Our results showed that the concentrations of soil total N, total P, available P, available K, and organic matter were all promoted by the OF treatment at the jointing stage of wheat, coinciding with the peak in egg hatching and penetration of wheat root by CCNs. Soil total N correlated positively (R2 = 0.759, p < 0.05) with wheat yields but negatively (R2 = 0.663, p < 0.01) with Pf/Pi (index of cyst nematode reproduction), implying the regulated soil property contributes to suppressing CCN in the OF treatment. Furthermore, fungal community α-diversity (Shannon and Simpson) and β-diversity (PCoA) of rhizosphere soil was improved under the organic fertilizer treatment. The fungal genera negatively associated with the Pf/Pi of CCN were highly enriched, which included Mortierella and Chaetomium, two taxa already reported as being nematophagous fungi in many other studies. These two genera were heavily surrounded by much more related fungal genera in the constructs co-occurrence network. These results suggested that the OF treatment shifted soil fungal community functioning towards the suppression of CCN. Taken together, the suppressed cyst nematode reproduction with the assembly of fungal communities in the rhizosphere led to greater wheat yields under organic fertilization. These findings provide an in-depth understanding of the benefits provided by organic fertilization for developing sustainable agriculture.